Learning Methods and Strategies in Islamic Education - Ajeng Novianti; Maspuroh; M. Fahri Mudzakir; Hesti Nurizkia; Salsabila Maulida (Penerbit Hellow Pustaka, 2025)
The task of educator is not only to deliver information to student but also to encourage them to be actively involved, thereby it can build independence and creativity in observing, analyzing and solving problems. In learning Islamic education, educator must strive to create learning environment conditions that can strengthen student learning. There are four elements in the Islamic education strategy, namely the formulation of clear goals, the selection of the right approach in the teaching and learning process, the formulation of learning steps, and benchmarks for learning success. Islamic education learning method can be classified into two kinds. Firstly, conventional method is a teaching method commonly used by educators or often referred to as traditional method. Secondly, the unconventional method, which is a newly developed teaching technique, such as the module teaching method, programmatic teaching, unit teaching, machine program, which was developed and applied in certain schools that have complete equipment and media as well as qualified educator.